MENINGKATKAN KUALITAS SDM GURU MELALUI PENGEMBANGAN DAN PELATIHAN DI SMA N 1 KALIANDA LAMPUNG SELATAN - Putri, Yola Arjunita; Patimah, Siti; Bedi, Fisman; Ayu, Sovia Mas; Junaidah, Junaidah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Training can make the human resources of educational institutions more competent and professional, while development aims to trigger human resources to channel their innovation and creativity. The writing of this scientific article uses a qualitative method. Data is obtained through observation, where the researcher functions as an instrument to make observations, in-depth interviews with primary data sources and study documentation. Based on the data from the research, educators at the school strongly support the existence of training programs in improving the quality of education. With training, human resources or educators can develop all aspects of their abilities in accordance with their main tasks and functions. The development of human resources or educators at SMA N 1 Kalianda, South Lampung Regency has been running well. However, the implementation of the training program has not been maximized, and the results obtained in the development of human resources or teaching staff at SMA N 1 Kalianda, South Lampung Regency need improvement actions in the implementation aspect. So that the training program that has been planned runs according to the desired expectations. Although something perfect is impossible, but in modern times like this, educational institutions or agencies are required to continue to try to maintain and improve what is their goal.